Convective heat transfer in thermally developing flow in micro-channels filled with porous media under local thermal non-equilibrium conditions. (August 2018) - Buonomo, Bernardo; Cascetta, Furio; Lauriat, Guy; Manca, Oronzio
Abstract: Thermally developing flow in microchannels or channels in rarefied gas filled with porous media in slip flow regime is numerically analyzed. A hydrodynamically fully developed and thermally developing flow of a dilute gas in a parallel-plate microchannel filled with porous media is carried out assuming the local thermal non-equilibrium (LTNE) condition for both the fluid and solid phases. The parallel walls are subjected to a constant heat flux.